Composite electrolytes and interface designs for progressive solid‐state sodium batteries - Junyu Hou; Tianke Zhu; Gang Wang; Rongrong Cheacharoen; Wu Sun; Xingyu Lei; Qunyao Yuan; Dalin Sun; Jie Zhao (Carbon Energy)
Abstract Solid‐state sodium batteries (SSSBs) are poised to replace lithium‐ion batteries as viable alternatives for energy storage systems owing to their high safety and reliability, abundance of raw material, and low costs. However, as the core constituent of SSSBs, solid‐state electrolytes (SSEs) with low ionic conductivities at room temperature (RT) and unstable interfaces with electrodes hinder the development of SSSBs. Recently, composite SSEs (CSSEs), which inherit the desirable properties of two phases, high RT ionic conductivity, and high interfacial stability, have emerged as viable alternatives; however, their governing mechanism remains unclear. In this review, we summarize the recent research progress of CSSEs, classified into inorganic–inorganic, polymer–polymer, and inorganic–polymer types, and discuss their structure–property relationship in detail. Moreover, the CSSE–electrode interface issues and effective strategies to promote intimate and stable interfaces are summarized. Finally, the trends in the design of CSSEs and CSSE–electrode interfaces are presented, along with the future development prospects of high‐performance SSSBs.